THE EMERGENCE OF UNIVERSALISM AND THE DECLINE OF SUPRANATIONALISM - Sigit Riyanto (Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractIn the context of addressing challenges of globalization there are many issues deserve to be discussed and elaborated. This paper addressed the three fundamental issues which are inseparable and interconnected each other: Spreading Universalism; Reinterpretation of Sovereignty, and the Decline of Supranationalism. The role of international organizations in the contemporary international system remain significant, however, constituents in the member States would judge whether they could maintain their relevance to the constituents interests and keep mutual relatianship with the member States.IntisariAda beragam persoalan yang layak diperdebatkan dan dijelaskan dalam mencermati tantangan globalisasi. Tiga persoalan mendasar dan saling terkait menjadi fokus bahasan dalam tulisan ini yakni: Universalisme yang makin meluas; re-interpretasi kedaulatan dan melemahnya supranasionalisme. Dewasa ini peran institusi internasional masih memiliki peran yang signifikan, namun, Negaranegara akan mencermati apakah institusi-isntitusi internasional ini mampu menjaga relevansinya terhadap kepentingan konstituen dan hubungan yangsaling menguntungkan dengan negara anggotanya.